Características audiológicas de indivíduos normo-ouvintes com queixas de zumbido e hiperacusia - Urnau, Daila (2011)
OBJECTIVES: to verify the occurrence and the effect of transient otoacoustic emissions (TEOAE), existence of association between: tinnitus degrees and hyperacusis degrees, TEOAE suppressive effect and laterality, tinnitus and hyperacusis degrees, and verify the characteristics of normal hearing individuals with complaints of tinnitus and hyperacusis. MATERIALS AND METHODS: The study included 25 normal hearing subjects having complaints of tinnitus and hyperacusis, with 16 female and nine male. About tinnitus, the subjects were asked about the location and tinnitus type and they completed the Tinnitus Handicap Inventory (THI), used for the classification of tinnitus degrees. A developed hyperacusis questionnaire and the questionnaire on handedness The assessment and analysis of handedness: The Edinburgh Inventor were completed too. They were tested about the research of Loudness Discomfort Level (degrees of hyperacusis), Acuphenometry and the suppression effect of otoacoustic emissions (TEOAE) in the frequencies of 1, 1.5, 2, 3 and 4 KHz. We used descriptive and statistical analysis of the data (Fisher exact test, Kruskal Wallis and Mann Whitney U and Spearman correlation). RESULTS: The occurrence of TEOAE ranged from 33 to 88%. We observed the presence of TEOAE suppression effect on 63.7% in the right ear and 81.7% in the left ear. There was no association between tinnitus degrees and hyperacusis degrees, and between the TEOAE suppression effect and laterality, degrees of tinnitus and hyperacusis degrees. About tinnitus, the most subjects reported acute pitch, in anamnesis and in Acuphenometry, bilateral location and mild degree. Women had degree of tinnitus statistically superior than men. The sounds considered uncomfortable were the high intensity ones and the reaction to the sounds most often cited were irritation, anxiety and need to depart from the sound. The difficulty in speech understanding at noise was mentioned. CONCLUSION: We conclude that the occurrence of TEOAE in these subjects was lower than that found in normal hearing subjects. A higher percentage of presence of TEOAE suppression effect has been found in both ears. Degrees of tinnitus and hyperacusis degrees were not correlated in normal-hearing individuals with complaints of tinnitus and hyperacusis, and there was no association between the TEOAE suppression effect and laterality and degrees of tinnitus and hyperacusis. The sample presented acute pitch, bilateral location and mild bilateral tinnitus.High intensity sounds were reported as uncomfortable and irritation was the most cited reaction of the sound.